Appendicitis in the Elderly Patient with Multiple Co-Morbid Conditions: Case Report - Rayamajhi, Anuj Jung; Paudel, Prashanta; Yadav, Rupesh Kumar; Paudel, Subash Chandra; Dhungel, Bidur Kumar; Byanjankar, Bikram; Pandit, Rabin (Birat Journal of Health Sciences, 2019)
Acute appendicitis is commonly encountered surgical emergency worldwide. Although, it is commonly found in young and middle aged groups, the incidence of the diseases in geriatric age group is very rare and possesses a great challenge to safe technique of anesthesia due to co-existing comorbid conditions and medications used. Geriatric population are more susceptible to complications of appendicitis. This is a case report of 82 years old male patient, presented with appendicular perforation with localized abscess formation in a septic state with multiple comorbid condition. Routinely performed Spinal and general anaesthesia adds further challenge in management of this patient during and after surgery. Therefore, we performed the case in regional nerve block; paravertebral, ilioinguinal- iliohypogastric (ILIH) and coeliac plexus block and sedation.